Catalyst for ammonia decomposition reaction, method for producing the same, and method for producing hydrogen using the same

JP7936940B2Active Publication Date: 2026-10-16KOREA RES INST OF CHEM TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025518836
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-01-20
Filing Date
2024-01-18
Publication Date
2026-10-16
Estimated Expiration
2044-01-18

AI Technical Summary

Benefits of technology

【0028】 本発明によるアンモニア分解反応用触媒の製造方法は、ルテニウム(Ru)をランタン-セリウム複合酸化物支持体に元素置換によって担持することにより、個別酸化物に元素置換によってルテニウムを担持した場合、又は湿式含浸及びディップコーティングなどの他の金属担持方法によって製造された触媒よりも高いアンモニア分解活性を有する触媒系を製造することができる。特に、成形支持体に対するルテニウムの担持において、より有用に活用することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007936940000004
    Figure 0007936940000004
  • Figure 0007936940000005
    Figure 0007936940000005
  • Figure 0007936940000006
    Figure 0007936940000006
Patent Text Reader

Abstract

The present invention relates to an ammonia decomposition catalyst, a method for producing the same, and a hydrogen production method using the same. More specifically, the present invention relates to a method for producing an ammonia decomposition catalyst, which can easily produce a catalyst that exhibits a higher ammonia conversion rate than conventional ammonia decomposition catalysts by economically and efficiently supporting highly active ruthenium on a lanthanum-cerium composite oxide support, an ammonia decomposition catalyst produced by the production method, and a hydrogen production method using the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalyst for ammonia decomposition reaction, a method for producing the same, and a method for producing hydrogen using the same, and more particularly, to a catalyst for ammonia decomposition reaction that can improve the ammonia conversion rate in the ammonia decomposition reaction, a method for producing the same, and a method for producing hydrogen using the same.

Background Art

[0002] In recent years, as climate change has intensified, hydrogen energy has attracted attention worldwide as an eco-friendly fuel to replace fossil fuels. For the practical application of hydrogen energy, it is important to develop technologies for safely and efficiently storing and transporting hydrogen. While there are various hydrogen storage methods, methods using hydrogen storage materials that can reversibly store and release hydrogen are expected as hydrogen storage media to be mounted on fuel cell vehicles.

[0003] One of the methods for efficiently storing and transporting hydrogen is to use ammonia as a hydrogen storage and supply source. Since the process of decomposing ammonia into hydrogen and nitrogen is an endothermic process, energy is required to obtain the products. Existing catalytic decomposition reactions require a large amount of heat to obtain a useful amount of hydrogen gas, which consumes significant costs for hydrogen production. 2NH3→3H2+N2 (Endothermic Reaction) …(1)

[0004] The catalyst for ammonia decomposition reaction is a catalyst that decomposes ammonia into nitrogen and hydrogen, and conventionally, there has been a problem that the conversion rate decreases when attempting to obtain high-purity hydrogen using the ammonia decomposition catalysts proposed so far.

[0005] In response to such actual circumstances, the present invention intends to propose a new ammonia decomposition catalyst having a high conversion rate from ammonia to nitrogen and hydrogen.

[0006] As a conventional technique, Japanese Patent No. 6381131 discloses a ruthenium-supported catalyst in which ruthenium is uniformly supported on a carrier containing basic magnesium carbonate that has a high specific surface area and a pore size distribution peak around 30 Å, which is produced by precipitating a magnesium compound and a ruthenium compound with an alkali metal carbonate in an aqueous solution, followed by drying, calcination and reduction.

[0007] In addition, Korean Patent No. 2303094 discloses a catalyst for ammonia decomposition having a structure in which ruthenium is substituted and bonded into the cerium lattice, which is produced by calcining a cerium precursor to prepare a cerium carrier, then supporting a ruthenium precursor such that ruthenium is contained in an amount of 1 to 10 parts by weight relative to 100 parts by weight of the cerium carrier, followed by drying and calcination.

[0008] However, these patents attempt to improve the catalytic activity of ruthenium by adding other active substances to the catalyst or modifying the carrier, and do not aim to improve the catalytic activity by changing the production method of the ruthenium catalyst as in the present invention.

[0009] On the other hand, in the industrial use of catalysts, a catalyst support is molded and used to address the pressure drop issue and improve usability. Regarding the loading of active metals on such supports, in consideration of the problem of active metal agglomeration due to the limited specific surface area of the catalyst support and mass transfer resistance, there is a demand for a more economical method for producing a catalyst for ammonia decomposition reaction that exhibits a high ammonia conversion rate.

[0010] The present invention improves the method for producing a catalyst for ammonia decomposition reaction, and provides a method for producing a catalyst having higher ammonia decomposition activity than existing production methods, and a catalyst obtained thereby. [Prior Art Documents] [Patent Documents]

[0011] [Patent Document 1] Japanese Patent No. 6381131 (Publication Date: September 5, 2016) [Patent Document 2] Korean Patent Publication No. 2303094 (Publication Date: January 20, 2021) [Overview of the Initiative] [Problems that the invention aims to solve]

[0012] The main object of the present invention is to provide a method for producing a catalyst for ammonia decomposition reactions that can easily produce a catalyst for ammonia decomposition reactions exhibiting excellent catalytic activity and a high ammonia conversion rate, and a catalyst for ammonia decomposition reactions produced by the method.

[0013] Furthermore, an object of the present invention is to provide a hydrogen production method that can efficiently produce hydrogen from ammonia using the ammonia decomposition reaction catalyst. [Means for solving the problem]

[0014] To achieve the above objective, one embodiment of the present invention provides a method for producing a catalyst for ammonia decomposition reaction, characterized by including an activated metal loading step in which a lanthanum-cerium composite oxide support is added to an activated metal precursor solution in which a ruthenium precursor is dissolved as an activated metal precursor, and then the activated metal in the precursor solution is subjected to an elemental substitution reaction with lanthanum and / or cerium of the lanthanum-cerium composite oxide support to support the activated metal on the lanthanum-cerium composite oxide support.

[0015] In one embodiment of the present invention, the active metal precursor solution in the active metal loading step may be characterized in that it contains a cesium precursor in addition to a ruthenium precursor.

[0016] Furthermore, the process may be characterized by adding a washing step to filter the supported material after the activated metal loading step by elemental substitution, and to remove inert substances and physically absorbed activated metal solutions present in the activated metal precursor of the filtered supported material.

[0017] A step of reducing the supported material with the activated metal in a reducing atmosphere may be added after the filtration and washing, and a step of drying the supported material with the activated metal obtained in the activated metal supporting step may be added before the reduction step.

[0018] In another embodiment of the present invention, the lanthanum-cerium composite oxide support added to the precursor solution in the ruthenium active metal loading step may be characterized by having cesium pre-supported on it.

[0019] In another embodiment of the present invention, a step of further supporting cesium may be included after the ruthenium active metal supporting step, wherein the cesium supporting method may be by impregnation, and the present invention may be characterized by performing one or more steps of drying, calcining, and reducing the lanthanum-cerium composite oxide support on which ruthenium is supported before the cesium supporting step.

[0020] As a preferred embodiment of the present invention, the lanthanum-cerium composite oxide support can be manufactured by a method comprising: (i) adding a lanthanum precursor and a cerium precursor to a solvent to obtain a lanthanum-cerium mixture; (ii) adding a basic substance to the obtained lanthanum-cerium mixture to generate a precipitate; (iii) filtering and washing the generated precipitate, and then drying it; (iv) calcining the dried precipitate to obtain a lanthanum-cerium composite oxide solid solution; and (v) molding the obtained lanthanum-cerium composite oxide solid solution, and then calcining it to obtain a lanthanum-cerium composite oxide support.

[0021] In a preferred embodiment of the present invention, the lanthanum-cerium composite oxide support may be characterized in that the molar ratio of lanthanum to cerium is 0.1:0.9 to 0.5:0.5.

[0022] In a preferred embodiment of the present invention, the elemental substitution can be characterized by being performed for 30 minutes to 24 hours.

[0023] In a preferred embodiment of the present invention, the reduction treatment may be characterized by heating to 300°C to 800°C in the presence of a reducing gas.

[0024] In a preferred embodiment of the present invention, the ammonia decomposition catalyst may contain 0.1% to 10% by weight of ruthenium and 0.01% to 10% by weight of cesium, based on the total weight of the catalyst.

[0025] Furthermore, the present invention provides a catalyst for ammonia decomposition reactions, characterized in that it is manufactured by the catalyst manufacturing method of the present invention and in which ruthenium is supported on a lanthanum-cerium composite oxide support by elemental substitution as the active metal.

[0026] Another embodiment of the present invention provides a catalyst for ammonia decomposition, characterized by containing ruthenium supported on a lanthanum-cerium composite oxide support, which is produced by the method for producing a catalyst for ammonia decomposition described above, and a method for producing hydrogen from ammonia in an ammonia decomposition reaction in the presence of the ammonia decomposition catalyst.

[0027] In another preferred embodiment of the present invention, the ammonia decomposition reaction may be carried out in the range of 300°C to 550°C. [Effects of the Invention]

[0028] The method for producing a catalyst for ammonia decomposition according to the present invention allows for the production of a catalyst system having higher ammonia decomposition activity than catalysts produced by supporting ruthenium (Ru) on a lanthanum-cerium composite oxide support by elemental substitution, or by other metal support methods such as wet impregnation and dip coating. In particular, it can be more useful in supporting ruthenium on molded supports.

[0029] Furthermore, the method for producing a catalyst for ammonia decomposition according to the present invention has the advantage of reducing wastewater generation and fundamentally preventing the reduction of catalytic activity due to unwanted compounds, by not using a separate reducing agent.

[0030] Furthermore, the ammonia decomposition catalyst produced by the aforementioned method can improve the ammonia conversion rate due to its high catalytic activity in the ammonia decomposition reaction, thereby enabling efficient production of hydrogen from ammonia. [Brief explanation of the drawing]

[0031] [Figure 1] This is a flowchart illustrating a method for producing an ammonia decomposition catalyst according to one embodiment of the present invention. [Figure 2a] The sample is prepared according to Example 1 of the present invention, and the STEM-EDS mapping image showing the distribution of Ru, Ce, La, and Cs atoms in the dried sample before the reduction step is shown. [Figure 2b] This image shows a STEM-EDS mapping image of the distribution of Ru, Ce, La, and Cs atoms in the catalyst produced by Example 1 of the present invention. [Figure 3] This graph shows the measurement results of the ammonia conversion rate of the catalysts produced in Example 1 and Comparative Examples 1-5 of the present invention, using the catalyst production method. [Figure 4] This graph shows the measurement results of the ammonia conversion rate of the catalysts produced in Example 12 and Comparative Examples 8 and 9 of the present invention, using the catalyst production method. [Figure 5]This graph shows the measurement results of the ammonia conversion rate by the catalyst support of the catalysts produced in Example 1 and Comparative Examples 6 and 7 of the present invention. [Figure 6] This graph shows the measurement results of the ammonia conversion rate of the catalysts produced in Examples 1 to 4 of the present invention. [Figure 7] This graph shows the measurement results of the ammonia conversion rate of the catalysts produced in Examples 5-7 of the present invention, based on the elemental substitution reaction temperature. [Figure 8] This graph shows the measurement results of the ammonia conversion rate of the catalysts produced in Examples 1 and 8 of the present invention. [Figure 9] This graph shows the measurement results of the ammonia conversion rate based on the elemental substitution reaction time of the catalysts produced in Examples 2, 7, and 9-11 of the present invention. [Figure 10] This graph shows the measurement results of the ammonia conversion rate by the cesium addition method of the catalysts produced in Examples 13 and 17-18 of the present invention. [Figure 11] This graph shows the measurement results of the ammonia conversion rate of the catalysts produced in Examples 12-16 of the present invention by the cesium addition method. [Modes for carrying out the invention]

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art in which the present invention pertains. Generally, the nomenclature used herein is well known and commonly used in the art.

[0033] As described herein, “elemental substitution reaction” means a reaction in which ruthenium is supported on a lanthanum-cerium composite oxide support by elemental substitution of cerium and / or lanthanum in the lanthanum-cerium composite oxide support due to the difference in reducing energy levels between the ruthenium and the lanthanum and / or cerium on the composite oxide.

[0034] Terms such as “equipped with,” “includes,” or “have” as used herein indicate the presence of features, figures, steps, actions, components, parts, or combinations thereof as described herein, and do not preclude the presence or addition of other features, figures, steps, actions, components, parts, or combinations thereof not mentioned herein.

[0035] This invention relates to a method for producing a catalyst for ammonia decomposition reactions, using ruthenium as the main active metal and a lanthanum-cerium composite oxide as a support.

[0036] Ruthenium is a well-known active metal in the ammonia decomposition reaction, but its activity in this reaction varies depending on the type of support and the method of support. In particular, the development of an optimal support method is necessary to efficiently and economically support ruthenium on molded supports.

[0037] The present invention is based on the discovery that when ruthenium is supported on a lanthanum-cerium composite support by an elemental substitution method, the ammonia decomposition activity can be increased compared to catalysts produced by using the respective oxide supports instead of a composite support, or by other metal support methods such as wet impregnation and dip coating.

[0038] More specifically, the present invention relates to a catalyst manufacturing method in which ruthenium, an active metal, is supported on a lanthanum-cerium composite oxide support by elemental substitution, thereby eliminating the need for a separate reducing agent and simplifying the active metal supporting process while providing a highly active ammonia decomposition catalyst and a method for manufacturing the same. In particular, it has been found to be an effective method for manufacturing a molded catalyst, leading to the completion of the present invention.

[0039] In the catalyst manufacturing method according to the present invention, a step of reducing the supported material with the active metal in a reducing atmosphere can be added after the active metal supporting step, and a step of drying the supported material with the active metal obtained in the active metal supporting step can be added before the reduction step.

[0040] In one embodiment of the present invention, in addition to ruthenium, cesium can be added as a co-catalyst as the active metal.

[0041] The present invention centers on the step of supporting ruthenium on a support containing a lanthanum-cerium composite oxide by elemental substitution, and when this step is included, the ammonia decomposition efficiency of the produced catalyst is higher compared to when ruthenium is supported by other methods.

[0042] Hereinafter, examples of preferred methods for producing the ammonia decomposition catalyst according to the present invention will be described in detail with reference to the attached drawings.

[0043] Figure 1 is a schematic process diagram of a method for producing a catalyst for ammonia decomposition reaction according to one embodiment of the present invention.

[0044] Referring to Figure 1, one embodiment of the present invention provides a method for producing a catalyst for ammonia decomposition, which may include the steps of first obtaining an active metal precursor solution in which a ruthenium precursor is dissolved as an active metal precursor, and then adding a lanthanum-cerium composite oxide support thereto to which the ruthenium is subjected to an elemental substitution reaction with the lanthanum and / or cerium of the lanthanum-cerium composite oxide support and supported on the support.

[0045] In this case, the ruthenium precursor may be one or more selected from the group including organic and inorganic compounds containing ruthenium ions. Specifically, it may be ruthenium chloride, hydrate, nitride, acetylacetonate, iodide, etc. Preferably, it may be ruthenium chloride such as RuCl3·xH2O or [Ru(NH3)6]Cl3.

[0046] The ruthenium precursor, as the active metal precursor, can be added to a solvent to uniformly disperse and support it on a lanthanum-cerium composite oxide support, as described later.

[0047] The solvent to which the ruthenium precursor is added can be any solvent capable of dissolving the ruthenium precursor, and for example, the solvent may be water, alcohols such as methanol and ethanol, or ketones such as acetone. The amount of the solvent can also be any amount capable of dissolving the ruthenium precursor.

[0048] The elemental substitution reaction according to the present invention is characterized by adding a lanthanum-cerium composite oxide support containing lanthanum and cerium to an active metal precursor solution, and then maintaining the solution in a manner that allows elemental substitution to occur, thereby substituting the active metal in the active metal precursor solution with the elements contained in the lanthanum-cerium composite oxide support through an elemental substitution reaction, thereby supporting the active metal on the lanthanum-cerium composite oxide support.

[0049] In the aforementioned elemental substitution reaction, after adding a lanthanum-cerium composite oxide support to the active metal precursor solution, the active metal in the active metal precursor solution is replaced by an elemental substitution reaction with the lanthanum and / or cerium contained in the support during the active metal loading step, without using a separate reducing agent, thereby enabling the active metal to be loaded onto the surface of the support.

[0050] Unlike wet impregnation, dip coating, and spraying methods, the aforementioned elemental substitution method does not artificially remove the solvent via a rotary evaporator, evaporator, or dryer. Instead, it allows for the elemental substitution of the active metal with elements in the support under specific reaction conditions, making it a particularly suitable method for supporting active metals on supports with limited surface area, such as molded pellets.

[0051] In this case, the element substitution reaction may be carried out at room temperature to 90°C, preferably 50°C to 90°C, and more preferably 50°C to 80°C for better loading efficiency. The substitution time may vary depending on the circumstances, but for example, it can be carried out for 30 minutes to 24 hours, preferably 1 to 18 hours, and even more preferably 3 to 15 hours. When the element substitution reaction temperature is above room temperature, the reaction rate of the element substitution reaction can be increased and the time required for element substitution can be shortened. When water is used as the solvent, solvent loss due to vaporization can be suppressed when carrying out the element substitution reaction at temperatures below 90°C.

[0052] Subsequently, the support material, in which the active metal is supported on the aforementioned lanthanum-cerium composite oxide support, can be filtered, washed, and then dried.

[0053] The aforementioned filtration, washing, and drying can be adequately carried out using methods and apparatus known in the art. Washing is performed to clean active metal precursors, inert substances, etc., that are not elementally replaced with lanthanum and / or cerium in the support and are physically attached to the surface of the support. There are no restrictions on the washing solvent used as long as it does not affect the activity, but it can be mainly carried out using water or alcohol. At this time, drying can be adjusted to 80°C to 150°C, preferably 90°C to 110°C, using a vacuum oven, hot air, constant temperature and humidity, microwave, etc. Such drying conditions should be understood as illustrative.

[0054] The dried support can be treated in a reducing atmosphere to produce a catalyst for ammonia decomposition.

[0055] The treatment in the reducing atmosphere is not limited as long as it can reduce the active metal, such as ruthenium, contained in the support. Examples include using reducing gases such as carbon monoxide, hydrocarbons, and hydrogen; or adding reducing agents such as hydrazine, lithium aluminum hydride, and tetramethylborohydride. When using reducing gases, they can also be diluted with other gases (e.g., nitrogen, carbon dioxide). Among these, reduction treatment using hydrogen as the reducing gas is preferred.

[0056] When using the reducing gas, heating can preferably be performed at a temperature of 300°C to 800°C, more preferably 400°C to 600°C, and the reduction treatment time can preferably be 0.5 hours to 5 hours, more preferably 1 hour to 3 hours. Prior to the reduction treatment with the reducing gas, an inert gas such as nitrogen or carbon dioxide can be used, and calcination can preferably be performed at a temperature of 200°C to 400°C for 1 to 7 hours.

[0057] If the aforementioned reduction treatment is performed, the active metal compound will, in principle, be converted into a metal that exhibits a zero valence state. If the reduction treatment is insufficient, the active metal compound will only be partially reduced, resulting in low catalyst activity. However, even in such cases, since hydrogen is generated during the ammonia decomposition reaction, the environment becomes the same as when the reduction treatment was performed. By continuing this reaction, the insufficiently reduced portion is reduced, becoming a zero-valence metal, and the catalyst can exhibit high activity.

[0058] The ammonia decomposition catalyst can support ruthenium as an active metal in an amount of 0.1% to 10% by weight relative to the total weight of the ammonia decomposition catalyst. When the ruthenium content in the ammonia decomposition catalyst is within the above range relative to the total weight of the catalyst, the activity of the ammonia decomposition catalyst can be further improved by sufficiently and economically supporting the active metal for the activation of ruthenium.

[0059] In one embodiment of the present invention, a firing step may be added after the drying, or the firing step may be performed immediately after the drying, or the drying step may be omitted and the reduction may be performed immediately.

[0060] On the other hand, the lanthanum-cerium composite oxide support can be used without limitation as long as it is a support containing lanthanum and cerium in predetermined amounts. For this reason, the lanthanum-cerium composite oxide support can be a commercially available product or manufactured and used, and any known manufacturing method in the art can be applied without limitation as a method for manufacturing the lanthanum-cerium composite oxide support.

[0061] As an example, the lanthanum-cerium composite oxide support can be manufactured by a method comprising: (i) adding a lanthanum precursor and a cerium precursor to a solvent to obtain a lanthanum-cerium mixture; (ii) adding a basic substance to the obtained lanthanum-cerium mixture to generate a precipitate; (iii) filtering and washing the generated precipitate, and then drying it; (iv) calcining the dried precipitate to obtain a lanthanum-cerium composite oxide solid solution; and (v) molding the obtained lanthanum-cerium composite oxide solid solution and then calcining it to obtain a lanthanum-cerium-containing molded catalyst support.

[0062] In detail, first, the lanthanum precursor and the cerium precursor are added to a solvent and mixed, and stirred to obtain a mixture of lanthanum and cerium precursors [(i) step].

[0063] The lanthanum precursor or cerium precursor may be one or more selected from the group including organic and inorganic compounds containing lanthanum or cerium ions. Specifically, at least one of the following can be used: oxides, chlorides, hydroxides, bromides, iodides, nitrates, sulfates, carbonates, acetates, oxalates, fluorides, isopropoxides, or organometallic complexes.

[0064] The lanthanum and cerium mixture thus obtained is subjected to the addition of a basic substance to produce a precipitate [(ii) step].

[0065] In this case, any basic substance that can precipitate lanthanum and cerium can be used without restriction, and one or more selected from ammonia, sodium hydroxide, potassium hydroxide, hydrazine, sodium carbonate, etc., can be used without restriction.

[0066] Subsequently, the precipitate produced is filtered, washed, dried in a vacuum oven or the like [(iii) step], and calcined to obtain a lanthanum-cerium composite oxide solid solution [(iv) step].

[0067] The drying in step (iii) can be carried out at 90°C to 110°C, and the calcination in step (iv) can be carried out in an air atmosphere at a temperature of 400°C to 700°C, preferably 500°C to 550°C, for 1 to 10 hours, preferably 3 to 5 hours, in order to obtain a lanthanum-cerium composite oxide solid solution.

[0068] The firing process in this invention can be carried out in a variety of known furnace types, such as tube furnaces, convection furnaces, and grate furnaces, and is not particularly limited.

[0069] In the case of molded bodies, when using a method to precipitate metal using a reducing agent, the presence of separate particles is undesirable. Methods that artificially remove the solvent through evaporators and dryers such as wet impregnation, spraying, and rotary evaporators are inefficient in terms of energy consumption. Dip coating, for example, has the problem of requiring repeated loading steps to achieve the desired content. Furthermore, additional steps are required after catalyst production to control inactive substances in the precursor. However, the ruthenium elemental substitution method of the present invention allows for the loading of ruthenium onto a limited surface area without a separate reducing agent because elements are substituted and exchanged with each other, thus simplifying the process. Therefore, the catalyst production method according to the present invention is particularly preferred in catalyst systems in which an active metal is loaded onto a molded support.

[0070] To obtain such a molded support, the lanthanum-cerium composite oxide solid solution obtained above can be molded by various molding methods such as injection molding, extrusion molding, vacuum forming, and casting, and then fired to obtain a lanthanum-cerium composite oxide support [(v) step].

[0071] When molding the lanthanum and cerium composite oxide solid solution, a catalyst mixture can be produced by mixing the lanthanum and cerium composite oxide solid solution with an inorganic binder, an organic binder, a solvent, etc., in predetermined amounts, before molding.

[0072] The inorganic binder, organic binder, and solvent mentioned above can be used without restriction as long as they are used in this field, and are not particularly limited. For example, the inorganic binder may be silica sol, alumina sol, titania sol, water glass, boehmite, etc., the organic binder may be cellulose, polyvinyl alcohol, polyethylene glycol, tyrose, starch, etc., and the solvent may be water, alcohols such as methanol and ethanol, ketones such as acetone, etc.

[0073] The calcination in step (v) above can be carried out in an oxidizing, reducing, or inert atmosphere at a temperature of 400°C to 700°C, preferably 500°C to 550°C, for 1 to 10 hours, preferably 3 to 5 hours, in order to remove binders, solvents, etc., while preventing changes in the crystal structure of the catalyst support.

[0074] The lanthanum-cerium composite oxide support manufactured in this manner has a lanthanum-cerium molar ratio of 0.1:0.9 to 0.5:0.5. When the lanthanum-cerium molar ratio satisfies the above range, the elements of the lanthanum and cerium composite oxide are dispersed amongst themselves. This composition provides the best electron transfer characteristics during the ruthenium substitution reaction, making it possible to produce a catalyst supported with a high ruthenium content in the support while exhibiting highly active ammonia degrading properties.

[0075] The method for producing an ammonia decomposition catalyst according to the present invention allows for the addition of a co-catalyst precursor to further support the co-catalyst.

[0076] In this case, the co-catalyst component may be cesium. The cesium can increase the electron density by providing electrons to catalytically active substances such as ruthenium in the ammonia decomposition reaction, thereby increasing the efficiency of the ammonia decomposition reaction by allowing nitrogen that has undergone dissociation adsorption, a crucial step in the reaction, to detach as nitrogen molecules.

[0077] When cesium is added as a co-catalyst in addition to ruthenium as a catalytically active substance, the cesium may be supported simultaneously with the ruthenium by elemental substitution, or it may be carried out before or after the ruthenium support.

[0078] The cesium is preferably supported by a method other than elemental substitution, more preferably by impregnation, and even more preferably by impregnation after ruthenium has been supported. When cesium is supported by elemental substitution, the cesium can be supported on the support together with ruthenium by including a cesium precursor in addition to the ruthenium precursor as an active metal precursor in the active metal precursor solution.

[0079] The solvent used to dissolve the active metal precursor at this time must be capable of simultaneously dissolving the ruthenium precursor and the cesium precursor, and the solvent may be water, alcohols such as methanol and ethanol, or ketones such as acetone, as mentioned above.

[0080] The cesium precursor may be at least one selected from the group including organic and inorganic compounds containing cesium ions. Specifically, it may be cesium chloride, hydrate, nitride, acetylacetonate, iodide, etc., and preferably a cesium nitride such as CsNO3.

[0081] The cesium may be supported separately before or after the ruthenium is supported by elemental substitution, and preferably the cesium may be supported after the ruthenium is supported. When cesium is supported on a lanthanum-cerium composite oxide support on which ruthenium is supported in this manner, the cesium can be supported after removing the solution filling the voids of the support by further performing at least one of drying, calcination, and reduction on the lanthanum-cerium composite oxide support on which ruthenium is supported after the ruthenium support step.

[0082] The cesium may be supported by a conventional support method, but preferably by impregnation.

[0083] The content of cesium, which is the co-catalyst component, can be determined considering the content of the catalytically active substance, and is preferably used at 0.01% to 10% by weight relative to the total weight of the catalyst, and more preferably at 0.5% to 5% by weight.

[0084] In other words, the present invention relates to a catalyst for ammonia decomposition, characterized by containing ruthenium supported on a lanthanum-cerium composite oxide support, which is produced by the above-described method for producing a catalyst for ammonia decomposition, and to a hydrogen production method for producing hydrogen from ammonia using the ammonia decomposition catalyst.

[0085] The ammonia decomposition catalyst produced by the manufacturing method of the present invention has a high degree of dispersion of the active metal for ammonia decomposition, and due to the strong interaction effect between the active metal for ammonia decomposition and the metal oxide of the catalyst support, catalytic activity, thermal stability and durability are all improved, thereby improving the ammonia conversion rate in the ammonia decomposition reaction.

[0086] Furthermore, the hydrogen production method according to the present invention can produce hydrogen by treating an ammonia-containing gas using the above-mentioned ammonia decomposition reaction catalyst, and dehydrogenating and decomposing the ammonia into nitrogen and hydrogen. [Examples]

[0087] The present invention will be described in more detail below through specific examples. The following examples are merely illustrative to aid in understanding the present invention, and the scope of the present invention is not limited thereto.

[0088] <Example 1> 1-1: Preparation of a lanthanum-cerium composite oxide support 75.7 g of cerium nitrate hydrate and 37.7 g of lanthanum nitrate hydrate were added to 1 L of distilled water and mixed and stirred to prepare a homogeneous aqueous solution. To this solution, 1 mole of aqueous ammonia was added dropwise until the pH reached 11 to form a precipitate. After filtering and washing the precipitate, it was dried in a vacuum oven at 110°C for 12 hours. The dried precipitate was crushed and treated in a calcinerator at 500°C for 3 hours under an air atmosphere to produce a lanthanum and cerium composite oxide solid solution, La 0.33 Ce 0.67 O 1.84 The obtained lanthanum-cerium composite oxide solid solution was mixed with 1 g of organic binder and 12 g of water, and then molded into pellets with a diameter of 2 mm and a length of 3 mm using an injection molding machine. The molded pellets were fired in a 500°C oven for 3 hours to obtain a lanthanum-cerium composite oxide support.

[0089] 1-2: Production of catalysts for ammonia decomposition reaction 0.936 g of ruthenium chloride hydrate and 0.89 g of cesium nitrate hydrate were added to 15 mL of distilled water, and then 12 g of the lanthanum-cerium composite oxide support obtained in Example 1-1 was added. The additive was maintained at 80°C for 6 hours, and the ruthenium from the ruthenium chloride hydrate was supported on the lanthanum-cerium composite oxide support by an elemental substitution reaction with lanthanum and / or cerium of the lanthanum-cerium composite oxide. The supported material was filtered and washed, and then dried in a vacuum oven at 110°C for 12 hours. The dried precipitate was treated at 500°C for 3 hours under a 100% hydrogen atmosphere to obtain a catalyst for ammonia decomposition (Ru-Cs / La) with 2.91 wt% ruthenium supported. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0090] <Example 2> After adding 1.82 g of ruthenium chloride hydrate and 1.72 g of cesium nitrate hydrate to 25 mL of distilled water, the same procedure as in Example 1 was carried out except that 12 g of the lanthanum-cerium composite oxide support obtained in Example 1-1 was added, to produce an ammonia decomposition reaction catalyst with 3.34 wt% of ruthenium supported thereon (Ru-Cs / La 0.33 Ce 0.67 O 1.84 ) was produced.

[0091] <Example 3> After adding 0.52 g of ruthenium chloride hydrate and 0.49 g of cesium nitrate hydrate to 25 mL of distilled water, the same procedure as in Example 1 was carried out except that 12 g of the lanthanum-cerium composite oxide support obtained in Example 1-1 was added, to produce an ammonia decomposition reaction catalyst with 0.68 wt% of ruthenium supported thereon (Ru-Cs / La 0.33 Ce 0.67 O 1.84 ) was produced.

[0092] <Example 4> After adding 1.04 g of ruthenium chloride hydrate and 0.98 g of cesium nitrate hydrate to 25 mL of distilled water, the same procedure as in Example 1 was carried out except that 12 g of the lanthanum-cerium composite oxide support obtained in Example 1-1 was added, to produce an ammonia decomposition reaction catalyst with 1.07 wt% of ruthenium supported thereon (Ru-Cs / La 0.33 Ce 0.67 O 1.84 ) was produced.

[0093] <Example 5> The same procedure as in Example 2 was carried out except that the element substitution reaction was performed at 25°C for 24 hours, to produce an ammonia decomposition reaction catalyst with 1.79 wt% of ruthenium supported thereon (Ru-Cs / La 0.33 Ce 0.67 O 1.84 ) was produced.

[0094] <Example 6> The same procedure as in Example 2 was carried out except that the element substitution reaction was performed at 50°C for 24 hours, to produce an ammonia decomposition reaction catalyst with 3.06 wt% of ruthenium supported thereon (Ru-Cs / La 0.33 Ce0.67 O 1.84 They manufactured ).

[0095] <Example 7> Except for carrying out the elemental substitution reaction at 80°C for 24 hours, the ammonia decomposition catalyst (Ru-Cs / La) containing 3.34 wt% ruthenium was prepared in the same manner as in Example 2. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0096] <Example 8> Except for carrying out the elemental substitution reaction at 90°C for 6 hours, the ammonia decomposition catalyst (Ru-Cs / La) containing 3.39 wt% ruthenium was prepared in the same manner as in Example 1. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0097] <Example 9> Except for carrying out the elemental substitution reaction at 80°C for 1 hour, the ammonia decomposition catalyst (Ru-Cs / La) with 1.92 wt% ruthenium supported was prepared in the same manner as in Example 2. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0098] <Example 10> Except for carrying out the elemental substitution reaction at 80°C for 3 hours, the ammonia decomposition catalyst (Ru-Cs / La) with 2.82 wt% ruthenium supported was prepared in the same manner as in Example 2. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0099] <Example 11> Except for carrying out the elemental substitution reaction at 80°C for 12 hours, the catalyst for ammonia decomposition (Ru-Cs / La) was prepared in the same manner as in Example 2, with 3.62 wt% ruthenium supported. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0100] <Example 12> Except for the absence of cesium, the ammonia decomposition catalyst (Ru / La) was prepared in the same manner as in Example 1, with 2.84 wt% ruthenium supported. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0101] <Example 13> 13-1: Ruthenium support 0.936 g of ruthenium chloride hydrate was added to 15 mL of distilled water, and then 12 g of the lanthanum-cerium composite oxide support obtained in Example 1-1 was added. The additive was maintained at 80°C for 6 hours, and ruthenium from the ruthenium chloride hydrate was supported on the lanthanum-cerium composite oxide support by an elemental substitution reaction with lanthanum and / or cerium of the lanthanum-cerium composite oxide. The supported material was filtered and washed, and then dried in a vacuum oven at 110°C for 12 hours.

[0102] 13-2: Cesium carrying A cesium nitrate aqueous solution prepared by adding 0.35 g of cesium nitrate hydrate to 15 ml of distilled water, and a stirred solution of the dried ruthenium chloride-supported lanthanum-cerium composite oxide support obtained in 13-1, were used in a rotary evaporator to artificially evaporate the water while rotating at 150 rpm at 50°C and a pressure of 72 mbar, thereby supporting cesium ions on the catalyst surface. The mixture was then placed in a vacuum oven and dried at 110°C for 12 hours. This dried precipitate was treated at 500°C for 3 hours under a 100% hydrogen atmosphere to produce a catalyst for ammonia decomposition (CS / Ru / La). 0.33 Ce 0.67 O 1.84 They manufactured ).

[0103] <Example 14> A catalyst for the ammonia decomposition reaction was prepared in the same manner as in Example 13, except that 0.175 g of cesium nitrate hydrate was used.

[0104] <Example 15> A catalyst for the ammonia decomposition reaction was prepared in the same manner as in Example 13, except that 0.525 g of cesium nitrate hydrate was used.

[0105] <Example 16> A catalyst for the ammonia decomposition reaction was prepared in the same manner as in Example 13, except that 0.7 g of cesium nitrate hydrate was used.

[0106] <Example 17> A catalyst for ammonia decomposition was prepared in the same manner as in Example 1, except that 0.35 g of cesium nitrate hydrate was added.

[0107] <Example 18> Except for first supporting and drying cesium via wet impregnation, and then using the resulting dried material to carry out an elemental substitution reaction with ruthenium, the ammonia decomposition catalyst (Ru / Cs / La) was used in the same manner as in Example 13. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0108] <Comparative Example 1> An aqueous ruthenium precursor solution, prepared by adding 0.936 g of ruthenium chloride hydrate and 0.89 g of cesium nitrate hydrate to 15 ml of distilled water, was spray-coated onto 12 g of the lanthanum-cerium composite oxide support obtained in Example 1-1. The support was then dried in a vacuum oven at 110°C for 12 hours. The dried material was then treated at 500°C for 3 hours under a 100% hydrogen atmosphere to produce a catalyst for ammonia decomposition (Ru-Cs / La) with 2.98 wt% ruthenium supported. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0109] <Comparative Example 2> To an aqueous ruthenium precursor solution prepared by adding 0.936 g of ruthenium chloride hydrate and 0.89 g of cesium nitrate hydrate to 15 mL of distilled water, 12 g of the lanthanum-cerium composite oxide support obtained in Example 1-1 was added. The stirred solution was then artificially evaporated using a rotary evaporator at 50°C and a pressure of 72 mbar at 150 rpm to support the ruthenium ions on the catalyst surface. The solution was then dried in a vacuum oven at 110°C for 12 hours. The dried material was then treated at 500°C for 3 hours under a 100% hydrogen atmosphere to obtain a catalyst for ammonia decomposition (Ru-Cs / La) with 3.17 wt% ruthenium supported. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0110] <Comparative Example 3> To an aqueous ruthenium precursor prepared by adding 0.936 g of ruthenium chloride hydrate and 0.89 g of cesium nitrate hydrate to 15 ml of distilled water, 12 g of the lanthanum-cerium composite oxide support obtained in Example 1-1 was added, and the metal aqueous solution was absorbed and supported for 30 seconds. Then, it was dried in an oven at 103°C for 1 hour, and then dried in a vacuum oven at 110°C for 12 hours. The dried material was treated at 500°C for 3 hours under a 100% hydrogen atmosphere to obtain a catalyst for ammonia decomposition (Ru-Cs / La) with 2.32 wt% ruthenium supported. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0111] <Comparative Example 4> The ammonia decomposition catalyst produced in Comparative Example 3 was absorbed and supported, and the process of drying it in an oven at 103°C for 1 hour was repeated a total of three times to produce an ammonia decomposition catalyst (Ru-Cs / La) with 3.61 wt% ruthenium supported. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0112] <Comparative Example 5> The ammonia decomposition catalyst produced in Comparative Example 3 was absorbed and supported, and the process of drying it in an oven at 103°C for 1 hour was repeated a total of five times, resulting in an ammonia decomposition catalyst (Ru-Cs / La) with 4.65 wt% ruthenium supported. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0113] <Comparative Example 6> The ammonia decomposition catalyst was prepared in the same manner as in Example 1, but instead of cerium nitrate hydrate and lanthanum nitrate hydrate in the preparation of the support in Example 1-1, only 113.2 g of lanthanum nitrate hydrate was used and added to 1 L of distilled water to produce an ammonia decomposition catalyst (Ru-Cs / La2O3) with 0.86 wt% ruthenium supported.

[0114] <Comparative Example 7> The ammonia decomposition catalyst was prepared in the same manner as in Example 1, but instead of cerium nitrate hydrate and lanthanum nitrate hydrate in the preparation of the support in Example 1-1, only 113.5 g of cerium nitrate hydrate was used and added to 1 L of distilled water to produce an ammonia decomposition catalyst (Ru-Cs / CeO2) with 1.55 wt% of ruthenium supported.

[0115] <Comparative Example 8> Except for the absence of cesium, a 3.05 wt% ruthenium-supported ammonia decomposition catalyst (Ru / La) was prepared in the same manner as in Comparative Example 1. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0116] <Comparative Example 9> Except for the absence of cesium, a ruthenium-supported ammonia decomposition catalyst (Ru / La) was prepared in the same manner as in Comparative Example 4. 0.33 Ce 0.67 O 1.84 They manufactured ).

[0117] [Table 1]

[0118] [Table 2]

[0119] <Experimental Example 1: Analysis of Catalytic Properties> To observe the microstructure of the catalysts produced in the examples, STEM-EDS analysis was performed on the catalyst produced in Example 1, and the results are shown in Figure 2.

[0120] As shown in Figure 2a, it was confirmed that the surface of the dried catalyst produced by Example 1 before the reduction process showed that ruthenium was uniformly dispersed within the lanthanum and ceria lattice due to elemental substitution of lanthanum and ceria.

[0121] Furthermore, as shown in Figure 2b, the catalyst produced in Example 1, when heat-treated via a reduction process, allowed ruthenium to rise to the surface and form particles. These particles were 3 nm or smaller and uniformly dispersed on the catalyst surface. This confirmed that the active metal ruthenium was uniformly supported on the catalyst surface through an elemental substitution reaction.

[0122] <Experimental Example 2: Measurement of catalytic activity using ruthenium-supported method> The ammonia conversion rates were measured by carrying out the ammonia decomposition reactions using the catalysts produced in Example 1 and Comparative Examples 1-5. The measurements were performed at atmospheric pressure with an ammonia space velocity of 3,000 ml / g. cat. The ammonia resolution was measured under conditions of / h and reaction temperatures of 300°C, 350°C, 400°C, 450°C, 500°C, and 550°C, and the results are shown in Figure 3.

[0123] Furthermore, in order to compare the catalytic activity of the ruthenium-supported method when cesium is not added as a co-catalyst, the Ru produced in Example 12, Comparative Example 8, and Comparative Example 9 were subjected to the ammonia decomposition reaction of catalysts produced by elemental substitution, spraying, and dip coating, respectively, as described above, and the results are shown in Figure 4.

[0124] As shown in Figures 3 and 4, the catalysts of Example 1 and Example 12, in which ruthenium was supported by elemental substitution, exhibit even better ammonia decomposition activity in the low-temperature range below 450°C compared to catalysts produced by different support methods.

[0125] This is presumably because, in the case of loading methods such as wet impregnation, spraying, and dip coating, the active metal is loaded at a high concentration during loading compared to elemental substitution according to the present invention, which increases the likelihood of the elements clumping together, and thus reduces the effectiveness of the interaction between the active metal and the support.

[0126] <Experimental Example 3: Measurement of ruthenium loading and catalytic activity using a support> The ammonia conversion rates were measured by carrying out the ammonia decomposition reactions using the catalysts produced in Example 1 and Comparative Examples 6-7. The measurements were performed at atmospheric pressure with an ammonia space velocity of 3,000 ml / g. cat. The ammonia resolution was measured under conditions of / h and reaction temperatures of 300°C, 350°C, 400°C, 450°C, 500°C, and 550°C, and the results are shown in Figure 5.

[0127] As shown in Figure 5, the catalyst produced in Example 1 exhibits superior ammonia decomposition capabilities across the entire temperature range compared to Comparative Examples 6 and 7.

[0128] Furthermore, referring to Table 1, it can be seen that the amount of ruthenium supported in Comparative Example 6, where the support was made solely of lanthanum oxide, and Comparative Example 7, where the support was made solely of cerium oxide, was far greater than the arithmetic average of the supported amounts of the individual lanthanum oxide and cerium oxide supports under the same loading conditions.

[0129] The above results suggest that in lanthanum-cerium composite oxides, there may be a separate ruthenium element substitution mechanism exhibiting a synergistic effect, rather than the individual ruthenium element substitution mechanisms in lanthanum oxide and cerium oxide. It is possible that this difference in ruthenium loading also influenced the difference in ammonia resolution between Example 1 and Comparative Examples 6 and 7.

[0130] <Experimental Example 4: Measurement of catalytic activity based on ruthenium content> The ammonia conversion rates were measured by carrying out each ammonia decomposition reaction using the catalysts produced in Examples 1 to 4. The measurements were performed at atmospheric pressure with an ammonia space velocity of 3,000 ml / g. cat. The ammonia resolution was measured under conditions of / h and reaction temperatures of 300°C, 350°C, 400°C, 450°C, 500°C, and 550°C, and the results are shown in Figure 6.

[0131] As shown in Figure 6, we were able to confirm that the ammonia resolution also increases as the ruthenium content increases at temperatures above 450°C.

[0132] <Experimental Example 5: Measurement of catalytic activity of elemental substitution reactions based on temperature> The ammonia conversion rates were measured by carrying out the respective ammonia decomposition reactions using the catalysts produced in Examples 1 and 5-8. The measurements were performed at atmospheric pressure with an ammonia space velocity of 3,000 ml / g. cat. The ammonia resolution was measured under conditions of / h and reaction temperatures of 300°C, 350°C, 400°C, 450°C, 500°C, and 550°C, and the results are shown in Figures 7 and 8.

[0133] As shown in Figure 7, the catalysts produced in Examples 6 and 7 exhibit superior ammonia decomposition capabilities at temperatures above 350°C compared to the catalyst in Example 5.

[0134] As shown in Figure 8, the catalyst produced in Example 1 exhibits superior ammonia decomposition capabilities compared to the catalyst produced in Example 8.

[0135] <Experimental Example 6: Measurement of Residues Based on Elemental Substitution Reaction Temperature> During the production of the catalysts in Examples 5-7, the filtered and washed solutions were collected during the ruthenium element substitution reaction in Examples 1-2 and measured using inductively coupled plasma (ICP), as shown in Table 3.

[0136] [Table 3]

[0137] As shown in Table 3, as the ruthenium loading temperature increased, the amount of residual ruthenium in the solution decreased, while the amounts of lanthanum and cerium increased. This means that ruthenium is substituted for lanthanum and cerium due to the reducing energy difference, and ruthenium is loaded onto the catalyst, while the substituted lanthanum and cerium are simultaneously ionized again. This indicates that as the temperature increases, a large amount of ruthenium can be loaded onto the catalyst surface through elemental substitution reactions.

[0138] <Experimental Example 7: Measurement of catalytic activity by elemental substitution reaction time> The ammonia conversion rates were measured by carrying out the respective ammonia decomposition reactions using the catalysts produced in Examples 2, 7, and 9-11. The measurements were performed at atmospheric pressure with an ammonia space velocity of 3,000 ml / g. cat. The ammonia resolution was measured under conditions of / h and reaction temperatures of 300°C, 350°C, 400°C, 450°C, 500°C, and 550°C, and the results are shown in Figure 9.

[0139] As shown in Figure 9, the catalysts produced in Examples 2, 7, and 9-11 showed high ammonia resolution, and in particular, the catalysts produced in Examples 2, 7, and 11 showed excellent ammonia resolution over the entire temperature range.

[0140] <Experimental Example 8: Measurement of catalytic activity based on cesium addition method and supported amount> The ammonia conversion rate was measured by carrying out an ammonia decomposition reaction using the catalysts produced in Examples 1 and 13-18. The measurement was performed at atmospheric pressure with an ammonia space velocity of 3,000 ml / g. cat. The ammonia resolution was measured under conditions of / h and reaction temperatures of 300°C, 350°C, 400°C, 450°C, 500°C, and 550°C, and the results are shown in Figures 10 and 11.

[0141] Referring to Figure 10, the catalyst in Example 13, in which Ru was supported by elemental substitution and then Cs was supported, used the same amount of cesium precursor, but showed superior ammonia decomposition compared to the catalyst in which both cesium and ruthenium were supported by elemental substitution (Example 17), and the catalyst in which cesium was first supported on the support and then ruthenium was supported by elemental substitution (Example 18).

[0142] Referring to Figure 11, the ammonia resolution changes as the ratio of ruthenium to cesium changes, and the catalyst produced by Example 13, in which cesium was supported at a ratio of 2:1 by weight relative to the support, showed the best ammonia resolution.

[0143] Therefore, the method according to the present invention, in the production of an ammonia decomposition catalyst using ruthenium as the active metal, can ensure high activity per unit catalyst volume by supporting a high content of ruthenium on a unit support while maintaining high catalytic activity. The catalyst produced thereby exhibits higher ammonia decomposition capabilities compared to existing catalysts, making it useful for industrial applications.

[0144] Although the present invention has been described with reference to the above-described examples, different embodiments can be constructed within the concept and scope of the invention. Therefore, the scope of the invention is defined by the appended claims and equivalents and is not limited by the specific embodiments described herein.

Claims

1. A method for producing a catalyst for ammonia decomposition reaction, An active metal loading step is performed in which a lanthanum-cerium composite oxide support is added to an active metal precursor solution in which a ruthenium precursor is dissolved as a precursor of the active metal, and then the active metal in the precursor solution is subjected to an elemental substitution reaction with lanthanum and / or cerium in the lanthanum-cerium composite oxide support to support the active metal on the lanthanum-cerium composite oxide support, and A method for producing a catalyst for ammonia decomposition reaction, characterized by comprising a washing step to filter the supported material after the active metal loading step, and to remove inert substances and physically absorbed active metal solutions present in the active metal precursor of the filtered supported material.

2. The method for producing a catalyst for ammonia decomposition reaction according to claim 1, characterized in that the active metal precursor solution in the active metal loading step also contains a cesium precursor in addition to the ruthenium precursor.

3. An additional step is to reduce the support on which the cleaned activated metal is supported in a reducing atmosphere. A method for producing a catalyst for ammonia decomposition reaction according to claim 1, characterized by the above.

4. The method for producing a catalyst for ammonia decomposition reaction according to claim 3, characterized in that a step of drying the support on which the active metal, which has been washed before the reduction, is added.

5. The method for producing a catalyst for ammonia decomposition reaction according to claim 1, characterized in that the lanthanum-cerium composite oxide support added to the precursor solution in the activated metal loading step is pre-supported with cesium.

6. A method for producing a catalyst for ammonia decomposition reaction according to claim 1, characterized in that the step of further supporting cesium is included after the active metal supporting step.

7. The method for producing a catalyst for ammonia decomposition reaction according to claim 6, characterized in that the cesium support is achieved by impregnation.

8. A method for producing a catalyst for ammonia decomposition reaction according to claim 7, characterized by performing one or more of the steps of drying, calcining, and reducing a lanthanum-cerium composite oxide support on which ruthenium is supported before the cesium is supported.

9. The lanthanum and cerium-containing molded catalyst support is (i) Adding a lanthanum precursor and a cerium precursor to a solvent to obtain a mixture of lanthanum and cerium, (ii) A step of producing a mixed precipitate of lanthanum and cerium with the lanthanum and cerium mixture obtained above, (iii) The step of filtering and drying the precipitate that has been produced, (iv) The step of calcining the dried precipitate to obtain a lanthanum and cerium composite oxide solid solution, (v) A method for producing a catalyst for ammonia decomposition reaction according to any one of claims 1 to 8, characterized in that it is produced by a method comprising the step of molding the obtained lanthanum and cerium composite oxide solid solution and then firing it to obtain a lanthanum and cerium-containing molded catalyst support.

10. The method for producing a catalyst for ammonia decomposition reaction according to claim 9, characterized in that the lanthanum-cerium composite oxide support has a molar ratio of lanthanum to cerium of 0.1:0.9 to 0.5:0.

5.

11. The method for producing an ammonia decomposition catalyst according to any one of claims 1 to 8, characterized in that the ammonia decomposition catalyst contains 0.1% to 10% by weight of ruthenium relative to the total weight of the catalyst.

12. The method for producing an ammonia decomposition catalyst according to any one of claims 1 to 8, characterized in that the ammonia decomposition catalyst contains cesium in an amount of 0.01% to 10% by weight relative to the total weight of the catalyst.

13. A method for producing hydrogen from ammonia by an ammonia decomposition reaction in the presence of an ammonia decomposition reaction catalyst manufactured by the method for producing an ammonia decomposition reaction catalyst according to any one of claims 1 to 8, wherein ruthenium is supported on a lanthanum-cerium composite oxide support as an active metal by elemental substitution.

14. The hydrogen production method according to claim 13, characterized in that the ammonia decomposition reaction is carried out in the range of 300°C to 550°C.

Citation Information

Patent Citations

  • Low-temperature ammonia decomposition hydrogen production catalyst, preparation method and application thereof

    CN111939907A

  • Telechelic polymer and production thereof

    JP1988081131A

  • Catalyst for hydrogen production through direct ammonia decomposition and its preparation method, and hydrogen pr℃ducing method using the same

    KR1020210007699A

  • Catalyst for Decomposing Ammonia and Method for Generating Hydrogen Using the Same

    KR1020220034652A

  • Catalyst for hydrogen production through direct ammonia decomposition and its preparation method, and hydrogen pr℃ducing method using the same

    KR102303094B1